Von Meyenburg complexes in a patient with chronic gastritis - a case report - Brodowski, Wojciech; Pawłowski, Piotr; Borowik, Joanna; Basta-Arciszewska, Katarzyna; Swora, Aleksandra; Bróż, Sebastian; Żelazny, Przemysław; Sygacz, Oliwer; Dankiewicz, Sara; Filipczak, Joanna (Journal of Education, Health and Sport, 2022)
Introduction: Bile ducts hamartoma (von Meyenburg complexes) is a common but unknown pathology of the liver. It can lead to the widening of the bile ducts. It is usually detected incidentally in asymptomatic patients. There are indications of transformation into bile duct cancer or hepatocellular carcinoma. Aim of the study: The aim of the study is to draw attention to a little known, but common pathology - von Meyenburg complexes and to sensitize medical professionals to the implications it may cause during the diagnostic process. Material and methods: We conducted a case study. The research material was the patient’s medical history. Case report: A 60-year-old man came to the Gastrology Clinic due to chronic epigastric pain and tenderness in the navel area. Colonoscopy ruled out pathology in the large intestine. After six months, the pain worsened. The result of the gastroscopy allowed the diagnosis of chronic gastritis, which was probably the cause of the problem. The abdominal ultrasound showed a suspicion of renal cell carcinoma of the right kidney, but the neoplastic process was excluded on the basis of the abdominal computed tomography. In the same study, for the first time, numerous minor hypodense lesions in the liver were detected. The final diagnosis was made on the basis of magnetic resonance cholangiography, where the disseminated, T2 hyperintense cystic areas were described. This suggested a biliary scythe. Conclusions: Despite the asymptomatic occurrence of biliary hamartoma, it is important to remember about the possible transformation into a malignant neoplasm. It should be considered in the differential diagnosis of disseminated liver lesions. Patients should be treated symptomatically.